30‐day hospital readmission following otolaryngology surgery: Analysis of a state inpatient database. (21st April 2016) - Graboyes, Evan M.; Kallogjeri, Dorina; Saeed, Mohammed J.; Olsen, Margaret A.; Nussenbaum, Brian
Abstract : Objectives/Hypothesis: Determine patient and hospital‐level risk factors associated with 30‐day readmission for patients undergoing inpatient otolaryngologic surgery. Study Design: Retrospective cohort study. Methods: We analyzed the State Inpatient Database (SID) from California for patients who underwent otolaryngologic surgery between 2008 and 2010. Readmission rates, readmission diagnoses, and patient‐ and hospital‐level risk factors for 30‐day readmission were determined. Hierarchical logistic regression modeling was performed to identify procedure‐, patient‐, and hospital‐level risk factors for 30‐day readmission. Results: The 30‐day readmission rate following an inpatient otolaryngology procedure was 8.1%. The most common readmission diagnoses were nutrition, metabolic, or electrolyte problems (44% of readmissions) and surgical complications (10% of readmissions). New complications after discharge were the major drivers of readmission. Variables associated with 30‐day readmission in hierarchical logistic regression modeling were: type of otolaryngologic procedure, Medicare or Medicaid health insurance, chronic anemia, chronic lung disease, chronic renal failure, index admission via the emergency department, in‐hospital complication during the index admission, and discharge destination other than home. Conclusion: Approximately one out of 12 patients undergoing otolaryngologic surgery had a 30‐day readmission. Readmissions occur across a variety of types of procedures and hospitals. Most of the variability was driven by patient‐specific factors, not structural hospital characteristics. Level of Evidence: 4. Laryngoscope, 2016 127:337–345, 2017